Convergence of Multiple Mechanisms of Steroid Hormone Action - Mani, S. K.; Mermelstein, P. G.; Tetel, M. J.; Anesetti, G. (Hormone and Metabolic Research, 2012)
Steroid hormones modulate a wide array of physiological processes including development, metabolism, and reproduction in various species. It is generally believed that these biological effects are predominantly mediated by their binding to specific intracellular receptors resulting in conformational change, dimerization, and recruitment of coregulators for transcription-dependent genomic actions (classical mechanism). In addition, to their cognate ligands, intracellular steroid receptors can also be activated in a “ligand-independent” manner by other factors including neurotransmitters. Recent studies indicate that rapid, nonclassical steroid effects involve extranuclear steroid receptors located at the membrane, which interact with cytoplasmic kinase signaling molecules and G-proteins. The current review deals with various mechanisms that function together in an integrated manner to promote hormone-dependent actions on the central and sympathetic nervous systems.
Keywords: estrogen; progesterone; signaling; cross-talk; ovary; brain